2015
DOI: 10.1016/j.celrep.2015.01.042
|View full text |Cite
|
Sign up to set email alerts
|

Epigenome Mapping Reveals Distinct Modes of Gene Regulation and Widespread Enhancer Reprogramming by the Oncogenic Fusion Protein EWS-FLI1

Abstract: SummaryTranscription factor fusion proteins can transform cells by inducing global changes of the transcriptome, often creating a state of oncogene addiction. Here, we investigate the role of epigenetic mechanisms in this process, focusing on Ewing sarcoma cells that are dependent on the EWS-FLI1 fusion protein. We established reference epigenome maps comprising DNA methylation, seven histone marks, open chromatin states, and RNA levels, and we analyzed the epigenome dynamics upon downregulation of the driving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
200
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 193 publications
(223 citation statements)
references
References 35 publications
(43 reference statements)
17
200
1
Order By: Relevance
“…The epigenetic profile of EWS has been directly linked to the activity of EWSR1-FLI1 [24,80] . EWSR1-FLI1 preferentially binds to sites with GGAA repeats, and classical ETS binding sites.…”
Section: Epigeneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The epigenetic profile of EWS has been directly linked to the activity of EWSR1-FLI1 [24,80] . EWSR1-FLI1 preferentially binds to sites with GGAA repeats, and classical ETS binding sites.…”
Section: Epigeneticsmentioning
confidence: 99%
“…Fusion of the N-terminal region of EWSR1, which contains a strong transcriptional activation domain [21,22] , and these DNA binding domains causes aberrant transcription of a multitude of genes. Additionally, EWSR1-ETS is known to affect epigenetic programs [23,24] , splicing [25,26] , and metabolic activity [27] of EWS. Oncogenic fusions between ETS genes and transcriptional activators are not unique to EWS: in 50%-70% of prostate cancers, similar chromosomal rearrangements are found [28] .…”
Section: Chromosomal Translocationsmentioning
confidence: 99%
“…Now it is possible to clearly perform an ES diagnosis in base of the presence of EWS/FLI1 (or a few functionally identical Editorial Rello-Varona & Tirado gene fusion variants). We know that EWS/FLI1 works as a transcription factor as well as a chromatin remodeler [10]. EWS/FLI1 action reprograms the cells, developing a cancerous phenotype.…”
mentioning
confidence: 99%
“…As a tumor entity that, apart from the EWS/FLI1 fusion, rarely shows recurrent mutations, any improvement in the knowledge of its epigenomic landscape becomes an important milestone [10]. In this sense, DNA methylation profiling provides meaningful data [4].…”
mentioning
confidence: 99%
“…As exemplarily demonstrated for EWS-FLI1 and ETS1, the SLFN11 promoter is highly promiscuous for ETS factor binding and activation, and the presented gene expression correlation analysis suggests that various different ETS factors may activate SLFN11 in a cell type-specific manner. A recent Ewing sarcoma epigenome study showed that EWS-FLI1 binding to promoters, in contrast to enhancers, is primarily associated with broadly active and widely expressed genes, where it acts predominantly as an amplifier of preexisting gene expression (4). In fact, in two model systems, human umbilical cord vascular endothelial cells and mouse embryonic superficial zone cells, ectopic expression of EWS-FLI1 led to the replacement of endogenous FLI1, respectively ERG, at ETS-driven promoters (5, 6), whereas knockdown of EWS-FLI1 resulted in its replacement from target promoters by ELF1 and GABPA ETS family members in a Ewing sarcoma cell line (7).…”
mentioning
confidence: 99%